Faktor Sosial Ekonomi Terhadap Tingkat Pengetahuan Infeksi Menular Seksual di Indonesia - Hamdani, Anita Fitri (STIKES Yayasan RS.Dr.Soetomo, 2025)
Sexually Transmitted Infections (STIs) are diseases that can be transmitted through sexual intercourse. STIs will be riskier if having sex with multiple partners, either vaginally, orally, or anally. The purpose of this study was to determine the level of knowledge about sexually transmitted infections in Indonesia. This study used data from the 2017 Indonesian Demographic and Health Survey with a cross-sectional research design where bivariate data analysis used chi square and multivariate analysis used logistic regression. The sample size of this study was 10,009 respondents with the study population being men and women in Indonesia. The results showed that respondents had a good level of knowledge about sexually transmitted infections. Sexually Transmitted Infections (STIs) are diseases that can be transmitted through sexual intercourse. STIs will be riskier if having sex with multiple partners, either vaginally, orally, or anally. The purpose of this study was to determine the level of knowledge about sexually transmitted infections in Indonesia. This study used data from the 2017 Indonesian Demographic and Health Survey with a cross-sectional research design where bivariate data analysis used chi square and multivariate analysis used logistic regression. The number of samples in this study was 10,009 respondents with a male and female study population in Indonesia. The results showed that around 2.3% of respondents had a low level of knowledge which was influenced by various factors including age (OR=0.764; 95%CI:0.656-0.891), gender (0R=1.085; 95%CL:0.841-1.399), wealth index (OR=2.847; 95%CI:2.543-3.186), education level (0R=3.377; 95%CI:2.561-4.453), place of residence (OR=0.525; 95%CI:0.468-0.588), and source of information (OR=17.974; 95%CI:13.156-24.556). From the results of this study, it is hoped that the Indonesian people can increase their knowledge by more actively seeking various sources of information and being more alert to the signs and symptoms of sexually transmitted diseases.